IMPROVEMENTS IN EFFICIENCY ARE BASED ON THE HIGH QUALITY OF LIVESTOCK PRODUCTION - Bahodirjon Nosirov; Akbarali Abdurashidov (Antis Publisher, 2024)
The production process of livestock products consists of clear, significantly different, and therefore strongly interrelated stages, which requires the creation and coordination of a comprehensive system of factors for the effective development of this industry. This field is interrelated, which embodies the technical, technological, biological, organizational, economic, social, political and legal directions of scientific and technical development, serves to increase the efficiency and quality of production of livestock products at various stages of the production process. And will have a tendency to develop as a result of the influence of important factors and their rational use..